Effect of Activators and Alizarin Dyes on Soap Flotation of Cassiterite and Fluorite - R. Schuhmann; Brahm Prakash (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1950)
Chemical conditions for flotation and nonflotation of cassiterite and fluorite with oleic acid as collector and with alizarin dyes as modifying agents were studied by means of small-scale, vacuum-flotation tests. Artificial cassiterite was prepared for these tests by high-temperature methods, especially by crystallization from borax melts.